An animal study on the effectiveness of platelet-rich plasma as a direct pulp capping agent - Dina M. Elkady; Yara R. Helaly; Hala W. El Fayoumy; Huda O. AbuBakr; Aya M. Yassin; Naglaa A. AbdElkader; Dina B. E. Farag; Possy M. Abd El Aziz; Antonio Scarano; Ahmad G. A. Khater (Scientific Reports, 2024)
Abstract Direct pulp capping (DPC) is a conservative approach for preserving tooth vitality without requiring more invasive procedures by enhancing pulp healing and mineralized tissue barrier formation. We investigated the effectiveness of Platelet Rich Plasma (PRP) vs. Mineral Trioxide Aggregate (MTA) as a DPC agent. Forty-two teeth from three mongrel dogs were divided into two equal groups. After three months, the animals were sacrificed to evaluate teeth radiographically using cone-beam computerized tomography, histopathologically, and real-time PCR for dentin sialophosphoprotein (DSPP), matrix extracellular phosphoglycoprotein (MEPE), and nestin (NES) mRNA expression. Radiographically, hard tissue formation was evident in both groups without significant differences (p = 0.440). Histopathologic findings confirmed the dentin bridge formation in both groups; however, such mineralized tissues were homogenous without cellular inclusions in the PRP group, while was osteodentin type in the MTA group. There was no significant difference in dentin bridge thickness between the PRP-capped and MTA-capped teeth (p = 0.732). The PRP group had significantly higher DSPP, MEPE, and NES mRNA gene expression than the MTA group (p < 0.05). In conclusion, PRP enables mineralized tissue formation following DPC similar to MTA, and could generate better cellular dentinogenic responses and restore dentin with homogenous architecture than MTA, making PRP a promising alternative DPC agent.